Washington rules : America's path to permanent war (New York : Metropolitan Books, 2010)
For the last half century, as administrations have come and gone, the fundamental assumptions about America's military policy have remained unchanged: American security requires the United States (and us alone) to maintain a permanent armed presence around the globe, and to be ready to intervene anywhere at any time. In the Obama era, just as in the Bush years, these beliefs remain unquestioned. In this vivid analysis, Andrew J. Bacevich presents the origins of this consensus, forged at a moment when American power was at its height. He exposes the preconceptions, biases, and habits that underlie our pervasive faith in military might, especially the notion that overwhelming superiority will oblige others to accommodate America's needs and desires--whether for cheap oil, cheap credit, or cheap consumer goods. And he challenges the usefulness of our militarism as it has become both unaffordable and increasingly dangerous.--From publisher description.
Includes bibliographical references : (pages [251]-269) and index.
Keywords: Consensus (Social sciences) -- United States; United States -- Foreign relations -- Decision making; United States -- Military policy -- Decision making